STEREOTIPE PEREMPUAN SEBAGAI PENGGODA PEMBACAAN ULANG Q.S. YUSUF: 23-24 - Siti Khotijah; Restu Amelia (Yayasan Baitul Hikmah al-Zain, 2024)
The position of women in societal structures is often framed as a object of sexuality. The stigma surrounding women as temptresses stems from cases in society, affirmed by the story of Zulaikha in the Quran. This research aims to reinterpret verses in the Quran used to legitimize the notion that, inherently, women possess the talent of seduction. The study employs a literature review approach with a qualitative descriptive method. The hermeneutical approach used is ma’na cum maghza by Sahiron Syamsuddin. The research data include interpretations of Surah Yūsuf verse 23-24 and other supporting data, such as a study of biological aspects.Through the reinterpretation of Surah Yūsuf verse 23-24, it is found that maghza of this ayah is not about the nature of women as temptresses existing since the time of the Prophet. The main message of the verse revolves around the resilience of Yūsuf as a Prophet in facing trials, including the temptation from women. Surah Yūsuf verse 23-24 is part of the exemplification of Yūsuf as a Prophet. This is because, biologically, both men and women have similar levels of sexual needs, with men being more visually stimulated and women being more emotionally drawn